Turnovers in the Construction Field in Uzbekistan - Abdurahmonov Adkhamjon Sultonboyevich; Tutiyo Egamberdiyeva (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
It's no secret that in recent years special attention has been paid to the development of the construction industry, like all other industries. As a result of the decrees and decisions of the government and the head of state aimed at further improving the system, the adopted state programs, ensuring their implementation, and the measures being taken to improve the effectiveness of reforms in the network, the scope of creativity is expanding. However, the beginning of a new era in the construction industry has not been easy to identify, recognize and disclose problems in the system, especially to solve them.